Integrasi Nilai – Nilai Islam dalam Pembelajaran IPAS di SDN Pekayon 03 Pagi - Zafira, Nadya Rahma; Heni Ani Nuraeni; Novi Amelia (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2025)
The integration of Islamic values ​​in science learning can foster a sense of awe and gratitude as well as a wise attitude towards nature to prove the greatness of God. There are not many studies that examine religious beliefs in gaining scientific knowledge in science learning and its direct application in learning. Therefore, this article aims to examine the integration of religious beliefs in acquiring knowledge in science and technology learning which has been carried out by elementary school teachers. The research uses a qualitative approach with observation and interviews as data sources, as well as qualitative descriptive data analysis. The results of the research show that teachers at SDN Pekayon 03 Pagi have connected Islamic values ​​with science material through apperception of the stories of the Prophet's friends and strengthening material related to God's power in nature. However, teachers face obstacles such as diversity in the classroom, time management, and availability of teaching materials.